Initial application of transanal endoscopic microsurgery for high-risk lower rectal gastrointestinal stromal tumor after imatinib mesylate neoadjuvant chemotherapy: A case report. Issue 29 (July 2017) - Liu, Qiaofei; Zhong, Guangxi; Zhou, Weixun; Lin, Guole
Abstract: Rationale: The lower rectal gastrointestinal stromal tumor (GIST) is a rare entity and warrants special attentions because of the considerations of preserving of anal and urinal functions. Neoadjuvant therapy with imatinib mesylate (IM) has achieved great success in GIST, which potentially extends the applications of function-preserving minimally invasive surgical procedures. Transanal endoscopic microsurgery (TEM) is a well-developed minimally invasive technique for benign tumors in lower rectum. Herein, we reported the initial application of TEM for high risk GIST after IM treatment. Patient concerns: A 52-year-old woman suffered mild lower abdominal pain and perianal discomfort. Physical examination found a soft mass 4 cm far away from anal verge. Rectal MRI and transrectal ultrasound (TRUS) showed that there was a 1.9 × 1.6 cm submucosal mass in the lower rectum. The incisional biopsy was performed and the pathological result reported it was a high-risk GIST. Diagnoses: High-risk lower rectal GIST. Interventions: IM was given for neoadjuvant therapy. Then TEM was adopted to resect the residual tumor. IM was restored 4 weeks after surgery. Outcomes: The final pathological results reported the margin was clear. After an 18-month follow up, no recurrence and metastasis was found and the patient had a satisfactory anal and urinal functions. Lessons: TEM in combination with IM could be a practical strategy for the high-risk lower rectal GIST simultaneously to achieve curative resection and to preserve the anal and urinal functions that can significantly improve the life quality of the patients.